Detection of extended spectrum beta-lactamase producing Gram-negative organisms: hospital prevalence and comparison of double disc synergy and E-test methods (IMC Journal of Medical Science, 2018)
Background and objectives: Emergence of extended spectrum beta-lactamase (ESBL) producing bacteria is a major public health concern. Detection of multi drug resistant (MDR) ESBL producing organisms is necessary to prevent its spread and effective treatment. The purpose of the present study was to determine the magnitude of ESBL producing organism in hospital setting and to compare the suitability of double disc synergy test (DDST) and cefepime-clavulanate E-test method for the detection of ESBL producing organisms in routine microbiology laboratory.Materials and methods: The study was carried out in the Department of Microbiology, Sir Salimullah Medical College, Dhaka from January 2011 to December 2011. Clinical samples included urine and pus from patients with suspected urinary tract and wound infections respectively. Standard microbiological methods were employed for isolation and identification of the organisms. DDST and E-test were used to detect ESBL producing Gram negative organisms.Results: A total of 186 Gram-negative organisms were isolated from various samples. Among the 186 Gram negative bacteria, 120 (64.5%) were Esch. coli while 33 (17.7%), 20 (10.8%) and 11 (5.9%) were Pseudomonas sp, Klebsiella sp and Proteus sp respectively. Out of total 186 isolates, 77 (41.4%) and 73 (39.2%) isolates were found ESBL producers by DDST and E-test method (p=0.674) respectively. Compared to Escherichia coli, Pseudomonas and Proteus, significantly high (p